Penerapan Model Pembelajaran Cooperative Integrated Reading and Composition (CIRC) untuk Meningkatkan Kemampuan Membaca Pemahaman di Kelas IV SDN 01 Lubuak Batingkok Kabupaten 50 Kota - Gayatry, Putry; Suriani, Ari; Azima, Nana Fauzana; Yenti, Yesni (Lembaga Yasin AlSys, 2025)
This study is motivated by the suboptimal implementation of reading activities in classroom instruction, which has led to low reading comprehension skills among fourth-grade students at SDN 01 Lubuak Batingkok, Lima Puluh Kota Regency. The aim of this study is to describe the application of the Cooperative Integrated Reading and Composition (CIRC) learning model in improving students’ reading comprehension abilities. This research is a Classroom Action Research (Penelitian Tindakan Kelas, PTK) conducted in two cycles, each consisting of four stages: planning, implementation, observation, and reflection. The subjects of the study were the teacher and 20 fourth-grade students. A combined qualitative and quantitative approach was used, with data collected through observation, tests, and non-test techniques. The results show a significant improvement across all observed aspects. The average quality of teaching module preparation increased from 88.5% in Cycle I to 97% in Cycle II. The implementation of teaching by the teacher and student engagement rose from 87.42% to 96.42%. Students' reading comprehension skills also improved, with the average score rising from 76.85% (categorized as fair) in Cycle I to 92% (categorized as very good) in Cycle II. Based on these findings, it can be concluded that the implementation of the CIRC model is effective in enhancing students' reading comprehension. The implications of this study indicate that literacy-based cooperative learning strategies can serve as a viable alternative for developing foundational literacy skills in elementary education.